2005
DOI: 10.1038/sj.bdj.4812353
|View full text |Cite
|
Sign up to set email alerts
|

Discharge of lubricant from air turbine handpieces

Abstract: O Ob bj je ec ct ti iv ve e To demonstrate and quantify the discharge of lubricating oil from high-speed air turbine handpieces whilst running. M Ma at te er ri ia al ls s a an nd d m me et th ho od ds s Dye-marked oil (Kavospray, KaVo) was used to lubricate four handpieces (Quiet-Air, Midwest) and the air discharged from around the lower bearing was directed at the moving chart paper on a recorder whilst running for 40 minutes. Secondly, seven new handpieces (Quiet-Air, 300SE, Midwest; Topair 796, Topair 795,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Moreover, the removal torque (RT) in rabbits varies for up to one month after implant placement, with little change thereafter. Additionally, previous research has shown that oil can continue to drain from the hand-piece for at least 240 min [45], implying that the exact amount of lubricant applied to the implant surface remains uncertain, thus necessitating reliance on estimates based on preliminary experiments [46]. Moreover, the use of only one type of lubricant rather than a variety of lubricants is another limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the removal torque (RT) in rabbits varies for up to one month after implant placement, with little change thereafter. Additionally, previous research has shown that oil can continue to drain from the hand-piece for at least 240 min [45], implying that the exact amount of lubricant applied to the implant surface remains uncertain, thus necessitating reliance on estimates based on preliminary experiments [46]. Moreover, the use of only one type of lubricant rather than a variety of lubricants is another limitation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the spray contents was discharged up to at least 240 min, but the amount of discharge was gradually reduced. 14 Their results suggested that uniform discharging of spray contents into entire the dentin surface might be difficult. In this study, therefore, the spray was applied directly in order to contaminate the dentin surface, referred to Rosa et al and Matos et al 18,19 Powers et al 15 and Knight et al 17 evaluated the handpiece lubrication on bond strength of enamel using two multi-step etch and rinse adhesive systems (All-Bond 2, Bisco; Optibond FL, Kerr; and Gluma 2000, Heraeus Kulzer), and they found that the significant difference between the mean bond strengths for the group prepared with a sterilized unlubricated handpiece and the group prepared with a lubricated handpiece.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation is that oil residue in the bearing was contaminated by water in the autoclaving. Because it is impossible to flush all excess oil by just 30 seconds of running after each lubrication, 12 if there is no loading during running, and thus no strong mechanical expulsion of this oil, then emulsification occurs which impairs elastohydrodynamic (EHD) film-forming ability since water does not increase in viscosity with pressure as do oils. 13,14 Furthermore, water retained in the oil is highly corrosive when the bearing is at rest and it lies at the contacts between components, causing contact corrosion.…”
Section: Damage Analysismentioning
confidence: 99%
“…This is a convenience, and also obviates flushing, as well as the delivery of oil in the patient's mouth and the risk to critical surfaces. 12 However, it is not clear how long the grease in the bearing can be effective. It is noted that one manufacturer offers a one-year warranty for a maintenance-free handpiece, but a two-year warranty for the equivalent model requiring lubrication.…”
Section: Damage Analysismentioning
confidence: 99%